2012
DOI: 10.1074/jbc.m112.416453
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Nucleotide and Aminoglycoside Substrate Specificity of the Bifunctional Aminoglycoside Acetyltransferase(6′)-Ie/Aminoglycoside Phosphotransferase(2″)-Ia Enzyme

Abstract: Background:The bifunctional AAC(6Ј)-Ie/APH(2Љ)-Ia enzyme was reported to phosphorylate all classes of aminoglycoside antibiotics using ATP. Results: GTP, and not ATP, is the cosubstrate of the enzyme. 4,5-disubstituted and atypical aminoglycosides are not substrates. Conclusion:The enzyme is a narrow spectrum GTP-dependent kinase that phosphorylates 4,6-disubstituted aminoglycosides exclusively. Significance: Knowledge of enzyme activity is essential for developing novel antibiotics and conducting effective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…Studies have revealed that most AACs are regiospecific and modify only one amine moiety on AGs, as often designated in their names. 23 One exception to this rule is Eis (enhanced intracellular survival), an AG multiacetylating protein upregulated in strains of Mycobacterium tuberculosis displaying resistance to KAN. 2431 Research has shown that some acetylated AGs, after being “inactivated” by AACs, still retain antibacterial activity. Therefore, having additional resistance enzymes that further modify AGs at different positions can help bacteria to completely inactivate AGs, avoiding toxic effects from these AG metabolites.…”
mentioning
confidence: 99%
“…Studies have revealed that most AACs are regiospecific and modify only one amine moiety on AGs, as often designated in their names. 23 One exception to this rule is Eis (enhanced intracellular survival), an AG multiacetylating protein upregulated in strains of Mycobacterium tuberculosis displaying resistance to KAN. 2431 Research has shown that some acetylated AGs, after being “inactivated” by AACs, still retain antibacterial activity. Therefore, having additional resistance enzymes that further modify AGs at different positions can help bacteria to completely inactivate AGs, avoiding toxic effects from these AG metabolites.…”
mentioning
confidence: 99%
“…Substrate profiling characterization revealed that the AAC(6′)-Ie domain displays broad substrate and cosubstrate profiles and tolerates a variety of AGs and acyl-CoA derivatives (Green et al, 2010). On the other hand, the APH(2″)-Ia domain interestingly displays very narrow substrate tolerance and exclusively utilizes GTP as a cosubstrate, not ATP, and only phosphorylates 4,6-disubstituted AGs, not 4,5-disubstituted AGs (Frase et al, 2012). …”
mentioning
confidence: 99%
“…Previously, Vakulenko and co-workers identified that only 4,6-disubstituted AGs are phosphorylated by the APH(2″)-Ia domain (Frase et al, 2012). At this point in time, it was still unclear how this selectivity was conferred by APH(2″)-Ia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this knowledge, a new nomenclature for the APH(2Љ) enzymes was proposed, which reclassified the APH(2Љ)-Ia, -Ib, -Ic, and -Id enzymes as APH(2Љ)-Ia, -IIa, -IIIa, and -IVa enzymes, respectively (8). Both APH(2Љ)-Ia and APH(2Љ)-IIIa utilize exclusively GTP as a cofactor, while APH(2Љ)-IIa and APH(2Љ)-IVa can utilize both ATP and GTP (8,9). At present, it is not known whether the ability to utilize GTP for phosphorylation of aminoglycoside antibiotics is limited to the aminoglycoside 2Љ-phosphotransferases or if the phenomenon is more widespread.…”
mentioning
confidence: 99%